DIRECTIONS FOR DEVELOPING POSTAL DIVERSIFICATION THROUGH DIGITALIZATION OF POSTAL COMMUNICATION ENTERPRISES IN UZBEKISTAN - G‘ulom , Mamatqulov (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This study explores the digital transformation of postal services within the Uzpost system through a unified management approach. It focuses on the integration of identification systems, personal account services, and domestic and international postal operations. The research shows that digital technologies improve service efficiency, enhance user convenience, and strengthen data security through centralized authentication. Additionally, digitalization enables remote service access, reduces physical visits to postal offices, and optimizes operational processes. Overall, the model contributes to improved service quality, revenue diversification, and the development of a modern digital postal infrastructure.